Comprometimento organizacional no serviço público: um estudo na seguridade social de Minas Gerais - Janaína Drummond de Carvalho (2015)
Organizations undergo constant changes due to the environmental demands that require capacity for change and adaptation before new scenarios that claim for diverse strategies of action. In the context, there are the Brazilian Public Institutions, entities with social function that seek the societys welfare instead of individual objectives wich require it adapt to the new management models originated after public management reform that transformed the Bureaucratic Public Administration in Management State. In this scenario, the organizational commitment is considered a key factor to organizational performance driving organizations to seek to understand the variables that determine the individuals involvement and strengthening the his bonds to it. Offering a contribution to the discussion of the subject, this work was carried on in a unit of the National Institute of Social Security (INSS) in Minas Gerais, an organization that runs the social security policy of the government, after a period of changes when the government employees career was restructured and new administrative tools of personnel management tools were adopted. This study can be characterized as a field, descriptive research using quantitative and qualitative approaches, involving, therefore, methodological triangulation. The data collection techniques an data analysis used documentary survey, whose secondary data were submitted to document analysis; questionnaires, whose primary data obtained were statistically tabulated using uni-variate and bivariate analysis, and semi-structured interviews, whose primary data were subjected to content analysis. In the first stage of research, predominated the affective dimension of organizational commitment, followed by the calculative dimension. Brivariate test conducted found differences between sample groups concerning gender, age, marital status, position, time in office an time in the organization. In the second stage of the research aspects predominate dating back to the calculative approach, followed by affective, little is expressed, and the normative, almost non-existent in the context studied. The study belongs to the research agenda on the topic in the field of organizational behavior studies, promoting reflection and analysis about the theme of commitment as an essential element in achieving organizational effectiveness.